(untitled) (Indian Journal of Arid Horticulture, 2025)
Fennel is an important high value seed spice crop belonging to family apiaceae. In India, the area under fennel is 74149 hectares with the total production of 114277 tonnes with an average productivity of 1541 kg ha (Anwer et al, 2011). It is mainly grown in Gujarat, Rajasthan, Karnataka, UP, Punjab and Haryana. The Gujarat contributes 80% of the total production in the country followed by Rajasthan (10%). In state like Rajasthan, area under fennel is spreading in semi arid regions but the productivity of the crop is low as compared to Gujarat. The yield potential of fennel is low primarily due to less availability of better genotype for cultivation under the prevailing agro-climatic conditions and secondly due to poor management of production sites (Singh et al, 2012)